Music as Text in the Works of Bulgakov - Andrews, Edna; Lowry, Yana (Recherches sémiotiques / Semiotic Inquiry, 2015)
The present article is a modest introduction to a larger theme that analyzes the use of music as text in the plays, short stories and novels of Mixail Bulgakov. The important contribution of Juri Lotman’s theoretical work on artistic space, the semiosphere, and the role of incorporating “texts within texts” (текст в тексте) is fundamental to our explication of the process of understanding Bulgakov’s use of music as text in a variety of its manifestations, resulting in an integrated and full-bodied textual structure that generates meanings critical to the works in which it is embedded. This analysis will focus on defining what “music as text” is for Bulgakov and specifically consider the use of music in the play, Zoya’s Apartment (Зойкина квартира).